Characterization of Streptomyces scabies isolates from potato tubers its pathogenic variations in Rawalpindi District - Shazia, S.; Naz, F.; Rauf, A.; Inam-ul-Haq, M.; Bushra, S. (Nepalese Journal of Biosciences, 2014)
Potato (Solanum tuberosum L.) has various biotic constraints in its production due to pest attack. Among these, common scab caused by streptomyces scabies is an important disease in potato which causes economic loss with respect to plant yield and quality of tubers. The present study was conducted to determine the pathogenicity, pathogenic variation, characterization of morphological, physiological and biochemical aspects of Streptomyces associated with potato tubers grown in Rawalpindi district. Severity data and pathogenic variation of disease was studied by using different isolation and characterization techniques.